2007
DOI: 10.1007/s10552-006-0106-7
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to low frequency magnetic fields and the risk of low grade and high grade glioma

Abstract: Our results do not support a role for occupational exposure to low frequency magnetic fields in the development of either LGG or HGG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 25 publications
0
5
0
3
Order By: Relevance
“…There have been many epidemiological studies of brain tumor risks in relation to occupational exposures to electric and magnetic fields, and most of such studies found no evidence to support the hypothesis that exposure to electric and magnetic fields is a risk factor for glioma [5,6,7]. …”
Section: Discussionmentioning
confidence: 99%
“…There have been many epidemiological studies of brain tumor risks in relation to occupational exposures to electric and magnetic fields, and most of such studies found no evidence to support the hypothesis that exposure to electric and magnetic fields is a risk factor for glioma [5,6,7]. …”
Section: Discussionmentioning
confidence: 99%
“…No se encontró un aumento en el riesgo de estos cánceres entre 28.224 sujetos con más de 3 meses de empleo, en quienes no se había diagnosticado cáncer antes del primer empleo. 35 realizaron un estudio de casos y controles con 414 casos histológicamente confirmados de glioma (diferenciados en alto y bajo grado) y 412 controles de Melbourne, Australia. Recolectaron la historia ocupacional detallada y estimaron la exposición ocupacional a CEM a través de 3 métodos: auto-reportado, revisión por un higienista experto y a través de una matriz de exposición laboral ( JEM).…”
Section: Base De Datosunclassified
“…During the past 20 years, a number of studies have examined the possibility that occupational exposure to hazardous chemical substances increases the risk for various diseases (Karipidis 2007). The incidence of environmental exposures on the general status of health has been increasingly acknowledged for numerous diseases (Melissa et al 2006).…”
Section: Soil and Groundwater Contaminationmentioning
confidence: 99%